RANCANG BANGUN GAME EDUKASI PENGENALAN HEWAN ENDEMIK INDONESIA MENGGUNAKAN CONSTRUCT 2 BERBASIS ANDROID - Yuda Suparmanto (Universitas Majalengka, 2022)
Indonesia has a very wide archipelago from the mainland to the mountains. The territory in the Indonesian archipelago contains various kinds of flora and fauna as well as microbes. Games are games. The game in this case refers to the notion of intellectual agility (Intellectual Playability Game) which can also be interpreted as an arena for decisions and actions of players, usually in a non-serious context or with the aim of refreshing. Educational Game is one type of media that is used to provide teaching, increase the knowledge of its users through a unique and interesting media. Puzzle games generally involve shapes, symbols or colors, and the player must arrange them into the correct pattern. Keyword : Flora, Fauna, Game, Puzzle game